Perancangan Sistem Kanban Pada Line Machining Yoke Di PT. Inti Ganda Perdana - Evan Hartono; Liem Yenny Bendatu (Jurnal Titra, 2015)
This paper discusses about the change of yoke line system production. Yoke line production uses push system, which is DPS (Daily Production Schedule) and assembling line process uses pull system, which is kanban. Pull system and push system in one flow process can cause problem in inventory fluctuation. The goal of this research is to change the production system yoke machining at PT Inti Ganda Perdana from current sistem DPS into kanban system. This change is done by using Part Information Flow Chart (PIFC) to illustrate the production flow and the formulation to compute the circulation of kanban population each month. The use of kanban cards will make yoke line production become pull system